Smart Campaign in Local Democracy Practices and Theory of Maqashid Sharia - Hawari, Nadirsah; Zaim, Muntaha bin Artalim; Agustam, Agustam (Universitas Islam Negeri Raden Intan Lampung, 2022)
Smart campaigns in this study are a number of campaign activities that are educative and solutive, especially when the community is in trouble due to a pandemic. The current difficult economic conditions, limited space for candidate campaigns and the existence of favored behavior in politics can become obstacles. On the other hand, the principle of siyasah syar'iyah and kaidah ushuliyah in politics must always be maslahah-oriented, especially the public interest, including the state. This study is in the form of analytical descriptive qualitative research, data collection techniques are in the form of observation, interviews, and documentation, while online media publications, documents from the success team are secondary sources, and conclusions are drawn using inductive thinking. The results of the study show that all candidates carry out various forms of smart campaigns so that the political reasoning and people's psychology remain healthy even though they are being hit by a pandemic. However, there are still some people who persist in a pragmatic style, oriented towards personal problems (al-mashlahah al-khassah) and ignore the general benefit (al-maslahah al-'ammah). According to them, accepting bribes, money politics, and distributing groceries are considered part of advancing mashlahah khasshah mudhtarrah (emergency) which can also be considered mashlahah 'ammah muhtamalah (predictive). Finally, this clashes with mashlahah 'ammah mutayaqqanah (definite benefit), the interests of the state and society for the realization of a welfare state within the framework of Pancasila democracy which begins with a clean and intellectual political process.